Communication Systems for Electrical Engineers - Matin, Mohammad A. (SpringerBriefs in Electrical and Computer Engineering, 2018)
This book is written as a very concise introduction for students taking a first course in communication systems. It provides the reader with fundamentals of digital communication systems and disseminates the essentials needed for the understanding of wire and wireless communication systems for Electrical Engineers. It covers important topics right from the beginning of the subject which communication engineers must understand. Example problems in each chapter will help them in understanding the materials well. The study of data networking will include multiple access, reliable packet transmission, routing and protocols of the internet. The concepts taught in class will be discussed in the context of aerospace communication systems: aircraft communications, satellite communications. The book includes example problems in each chapter to help the reader in understanding the materials well.